2020
DOI: 10.1007/s00706-020-02671-w
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective synthesis of 2-(2,4-dinitrophenyl)hydrazono- and (2-tosylhydrazono)-4-oxo-thiazolidine derivatives and screening of their anticancer activity

Abstract: Stereoselective synthesis of (Z)-methyl 2-[(Z)-3-substituted-2-(2-(2,4-dinitrophenyl)hydrazono)-4-oxothiazolidine-5-ylidine)]acetates and (Z)-methyl 2-[(Z)-3-substituted-2-(2-(tosylhydrazono)-4-oxothiazolidine-5ylidine)]acetates via the cyclization of N-substituted-2-arylhydrazinocarbothioamides with dialkyl acetylenedicarboxylates in absolute ethanol is reported. The structures were confirmed by spectroscopic data as well as single crystal X-ray analyses. The mechanism of nucleophilic addition and the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…The structures of the products were verified by X-ray crystallographic analysis. 19 In 2015, Sabbaghan and Yousefi reported a strategy to synthesize furan-2,3,4-tricarboxylates or 2-acetylfuran-3,4-dicarboxylates in high yields via the DABCO-catalyzed reactions of dialkyl acetylenedicarboxylates and ethyl bromopyruvate or -chlorocarbonyl compounds in the presence of K 2 CO 3 (1.5 mmol) and biphasic H 2 O-Et 2 O (1:1) as the solvent system at room temperature (Scheme 15). Ethyl bromopyruvate or the -chlorocarbonyl compound were used in three-fold excess with respect to the acetylenic ester and the reactions were complete in 1 hour.…”
Section: Scheme 12 Synthesis Of Dialkyl Aminomaleatesmentioning
confidence: 99%
“…The structures of the products were verified by X-ray crystallographic analysis. 19 In 2015, Sabbaghan and Yousefi reported a strategy to synthesize furan-2,3,4-tricarboxylates or 2-acetylfuran-3,4-dicarboxylates in high yields via the DABCO-catalyzed reactions of dialkyl acetylenedicarboxylates and ethyl bromopyruvate or -chlorocarbonyl compounds in the presence of K 2 CO 3 (1.5 mmol) and biphasic H 2 O-Et 2 O (1:1) as the solvent system at room temperature (Scheme 15). Ethyl bromopyruvate or the -chlorocarbonyl compound were used in three-fold excess with respect to the acetylenic ester and the reactions were complete in 1 hour.…”
Section: Scheme 12 Synthesis Of Dialkyl Aminomaleatesmentioning
confidence: 99%
“…32 Also, thiosemicarbazides are a vital class of organic compounds that operate as the backbone of a range of heterocyclic compounds of considerable interest in medical and industrial uses. 33,34 Additionally, interactions with phenacyl bromides revealed that thiosemicarbazides have several active centers. 35 Busby and Domincy were the rst to investigate the behavior of 4substituted thiosemicarbazides toward haloketones, obtaining 2-amino-1,3,4-thiadiazines.…”
Section: Introductionmentioning
confidence: 99%